Russian national model of public policy: structure and special features - D. Yu. Znamenskiy (Управление)
The subject of the study is the current model of formation and implementation of public policy in Russia. The purpose of this article is to analyze and develop a detailed description of the main distinguishing features of this model and to identify the factors that caused them. At the same time the author focuses on the political and cultural factor as the fundamental basis of the national model of public policy in any country. Among other components of the national model of public policy the institutional center for the adoption of political decisions, the features of the system of representation of interests, and the technology for making political decisions are singled out. Primary data were obtained as a result of an in-depth expert questionnaire as well as a focus-group interview.The article gives a detailed description of the Russian political culture, especially the perception by citizens of the main institutions of the political system (the state and its key institutions, political parties, socio-political organizations, etc.). At the same time, the author relies both on the results of previous studies in this area and on the latest data from Russian Public Opinion Research Center. The analysis of the peculiarities of citizens’ perception of the main political institutions made it possible to draw a conclusion about their direct connection with the specifics of the domestic system of political representation.The main theoretical result of the research is to substantiate the author’s approach to public policy research. It is proved that the public policy should be interpreted as the result of interaction of the state, civil society institutions, scientific, expert and business community with the decisive role of the former. No less important research result is the substantiation of the author’s understanding of the national model of public policy, its structure and features of manifestation in modern Russia. The practical significance of the results is due to the possibility of their use in the development of concepts, strategies and doctrines of public policy in various fields, as well as policy documents of political parties and other socio-political organizations.